A Comparison of Collaborative Information Retrieval (CIR) Behaviors of Two Design Teams - Bruce, Harry; Fidel, Raya, Annelise Mark Pejtersen; Dumais, Susan; Grudin, Jonathan; Poltrock, Steven (Information Seeking in Context (ISIC 2002), 2002)
The goal of the Collaborative Information Retrieval (CIR) Project is to study situations where members of a work-team are seeking, searching, and using information collaboratively. A field study of two design teams (one at Microsoft and the other at the Boeing Company), guided by the Cognitive Work Analysis has provided preliminary results. These show that: (a) the concept of CIR is illusive and does not easily lend itself to an operational definition; (b) work context has a strong effect on CIR behavior; and (c) not all activities relating to CIR are carried out collaboratively.